Dementia-related work activities of home care nurses and aides: Frequency, perceived competence, and continuing education priorities. Issue 2 (1st February 2016) - Morgan, Debra G.; Kosteniuk, Julie G.; O'Connell, Megan E.; Dal Bello-Haas, Vanina; Stewart, Norma J.; Karunanayake, Chandima
ABSTRACT: An understanding of the specific dementia learning needs of home care staff is needed to plan relevant continuing education (CE) programs and supports. The study's objective was to examine frequency and perceived competence in performing 20 dementia-related work activities, and identify CE priorities among home care staff. A cross-sectional survey of all home care staff in a primarily rural health region was used to gather data. Of 111 eligible staff, 82 participated (41 nursing aides, 41 nurses/case managers). To explore the relationship between activity frequency (F) and competence (C), the proportion of nurses and aides in four quadrants for each activity was examined: (1) low F-low C, (2) low F-high C, (3) high F-low C, and (4) high F-high C. Nurses/case managers were significantly more likely than aides to regularly perform 11 activities and to report high competence in 9 activities ( p < .05); aides were more likely to assist with two activities (personal care and daily living activities). Thus, nurses/case managers performed a broader range of activities and reported higher competence overall. The top CE topic for both groups was recognizing differences between dementia subtypes, but rankings for most activities varied by group. Aides' CE priorities indicated a desire to develop competence in low frequency-low competence activities, suggesting an expanded role in supporting dementia patients and their families. Nurses' CE priority topics were in the high F-high C quadrant, indicating a need to further develop competence in these activities. Findings have implications for planning CE programming for home care providers.